Recognizing Islam - Shahid Vawda (International Institute of Islamic Thought, 1996)
Michael Gilsenan is an anthropologist who has done extensive fieldwork in Egypt and Lebanon and has extensive knowledge of the literature, paticularly ethnography, on the Middle East, including North Africa. His book Recognising Islam is a detailed ethnography of the practice of Islam in the Middle East. When it was fi.rst published, it was considered a significant anthropological contribution to the understanding of the complexities of Islamic societies in the Middle East. To be more precise, it is about Islam as practiced in the villages and urban centers of Lebanon, Egypt, Morocco, Algeria, Libya, and Iran. These are the places from which he draws illustrative enthnographic material, weaving into the narrative his analysis of the specific case studies of urban and village !if e showing how Islam is practiced in the context of much larger national and international events taking place. The Islam that Gilsenan wishes to be recognized is not that of the literate specialists or of learned sheikhs. Neither is it of theological discussions and debate, although no doubt it has implications for those debates, nor is it of Orientalist conceptions or the Western media's caricature of Muslims as the inscrutable "other"----the barbarous, corrupt, enemy of Christianity, and nemesis of Western civilization. In other words, the focus on the practice of Islam in the villages of the Middle East and urban enclaves of such major cities as Cairo is not just a description of the exotic or strange practices of people as bounded entities, each one being an isolated species of Muslim groupings. Rather, Gilsenan's work shows how daily life is informed by ...